Application of SF-36 questionnaire to analyze the quality of life at work: a case study for a company in the region of Campinas/SP (Research, Society and Development, 2020)
The study aimed to analyze the quality of life index according to SF-36 methodology. This questionnaire was applied to employees of a company located in the region of Campinas/SP. The following scores were found: general health domain 61; vitality 73; mental health 74; emotional aspects 85; functional capacity 89; pain 91; social aspects 94; and physical aspects 96. It was concluded that, in general, the employees of the study company are young adults, mostly females, prevalent between 26 and 35 years old, and present favorable conditions in most of the domains researched. special attention to employees in a specific sector, according to the scoring and results table of the SF-36 questionnaire.